Shift work and perceived workplace breastfeeding support impacts on breastfeeding intention among female worker at manufacturing industry - Auni Najwa, Mawardi (2025)
The phenomena of shift work have attracted a lot of attention lately, especially in relation to its effects on mother’s health and breastfeeding intentions among working women. Characterised by non-standard work hours including night shifts and rotating schedules, shift work disturbs the natural biological cycles controlling many physiological functions. These challenges can lead to increased stress and exhaustion, which severely effect a mother’s intention and ability to breastfeed. This study investigates the impact of shift work and workplace support on breastfeeding intentions among female workers in manufacturing industry. We conducted a cross-sectional survey with 131 female workers (89 shift workers, 42 non-shift workers) at one aircraft composite manufacturing company in Malaysia. The results show that shift workers had significantly stronger intentions to breast- feed compared to non-shift workers, which is a surprising finding contrary to previous research. Mann-Whitney U test confirmed significant differences in all breastfeeding intention measures (p < 0.05). The night shift was identified as most challenging for breastfeeding by 43.8% of shift workers, while morning shift was most preferred (58.4%). Spearman correlation analysis found positive relationships between workplace support measures and breastfeeding intentions among shift workers. Linear regression analysis showed that workplace support significantly predicted breastfeeding intentions, explaining 18.2% of variance in 6-month exclusive breastfeeding intentions (0.43, p < .001). These findings suggest that with appropriate workplace support shift workers can maintain strong breastfeeding intentions. The study recommends enhanced support for night shift workers, establishment of designated nursing rooms, flexible break policies, and education for supervisors and coworkers.